2016
DOI: 10.1016/j.ebiom.2016.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Progranulin Recruits HSP70 to β-Glucocerebrosidase and Is Therapeutic Against Gaucher Disease

Abstract: Gaucher disease (GD), the most common lysosomal storage disease, is caused by mutations in GBA1 encoding of β-glucocerebrosidase (GCase). Recently it was reported that progranulin (PGRN) insufficiency and deficiency associated with GD in human and mice, respectively. However the underlying mechanisms remain unknown. Here we report that PGRN binds directly to GCase and its deficiency results in aggregation of GCase and its receptor LIMP2. Mass spectrometry approaches identified HSP70 as a GCase/LIMP2 complex-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
138
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(148 citation statements)
references
References 56 publications
10
138
0
Order By: Relevance
“…In further studies, the authors determined that progranulin is required to mobilize GCase to the lysosome in stress conditions, and that it binds directly to GCase and recruits HSP70 to form a complex involving LIMP‐2 to allow for final trafficking to the lysosome. A modified progranulin was found to reduce storage and increase lysosomal localization of GCase in patient fibroblasts (Jian et al., ). Progranulin has been proposed as a chaperone of other lysosomal enzymes, supporting the possible role of progranulin as a modifier of GD and lysosomal function in general (Jian, Hettinghouse, & Liu, ).…”
Section: Modifiers Of Gaucher Disease: Results Of Candidate Gene Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In further studies, the authors determined that progranulin is required to mobilize GCase to the lysosome in stress conditions, and that it binds directly to GCase and recruits HSP70 to form a complex involving LIMP‐2 to allow for final trafficking to the lysosome. A modified progranulin was found to reduce storage and increase lysosomal localization of GCase in patient fibroblasts (Jian et al., ). Progranulin has been proposed as a chaperone of other lysosomal enzymes, supporting the possible role of progranulin as a modifier of GD and lysosomal function in general (Jian, Hettinghouse, & Liu, ).…”
Section: Modifiers Of Gaucher Disease: Results Of Candidate Gene Studiesmentioning
confidence: 99%
“…Candidate modifiers have helped guide research into potential new therapeutic directions. For example, it was suggested that progranulin might serve as a target for treatment, based on preliminary studies in patient fibroblasts and PGRN‐deficient mice (Jian et al., ). Considering its critical role in GCase activation, LIMP‐2 also can be a potential target for therapy in not only GD, but also other neurological conditions.…”
Section: Modifiers As Targets For Therapeutic Strategiesmentioning
confidence: 99%
“…NCL and Gaucher diseases, in which PGRN is implicated, are lysosomal storage disorders. PGRN binds several lysosomal proteins such as sortilin, prosaposin, and β-glucocerebrosidase (Hu et al, 2010; Jian et al, 2016a; Zhou et al, 2015). Lysosomal proteins, which accumulate in NCL, have also been found to accumulate in FTLD-TDP patients with GRN mutations (Gotzl et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the endogenous growth factor progranulin (PGRN) was identified as a natural ligand of TNFRs in 2011 . This ubiquitous molecule has multiple functions, including significant roles in cell proliferation, wound healing, and regulation of immune responses . Interestingly, PGRN functions as a physiological antagonist of TNFR1 and a potent agonist of TNFR2 (with approximately 600‐fold higher binding affinity to TNFR2 than TNF).…”
Section: Selective Tnf Blockadementioning
confidence: 99%